DIGITAL ETHICS IN THE POST-TRUTH ERA: REVISITING IBN ‘ĀSYŪR’S INTERPRETATION OF KHUTUWĀT AL-SHAYṬĀN - Melisa Diah Maharani; Muhammad Ma’sum (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study explores digital ethics in the post-truth era by re-examining Ibn ‘Āsyūr’s interpretation of khutuwāt al-shayṭān (the steps of Satan). Employing a qualitative library research approach, it analyzes the primary text al-Taḥrīr wa al-Tanwīr alongside relevant contemporary literature. The findings indicate that Ibn ‘Āsyūr conceptualizes the steps of Satan as a gradual process that entices humans through subtle whispers until they become accustomed to deviant behavior. In today’s digital context, this idea resonates with algorithmic mechanisms of social media and the phenomenon of digital deception, which progressively cultivate bias, social polarization, and destructive patterns of behavior. The analysis highlights Ibn ‘Āsyūr’s emphasis on the necessity of self-control from the very outset. Accordingly, this research proposes the framework of a safeguarding fortress that integrates three interrelated dimensions: rational (critical thinking), psychological (self-regulation), and spiritual-ethical (moral awareness and divine guidance). Ultimately, digital ethics in the post-truth age cannot be sustained merely through technical literacy but must also be reinforced by a transcendental awareness that enables individuals to withstand the pervasive spread of informational illusions and disinformation.